Pregnancy Outcomes among Women with Class III Obesity with Pre-diabetic Early Hemoglobin A1C - Dillon, Jacquelyn; Mitchell, Courtney J.; Ellett, Tressa; Siegel, Anne; Denoble, Anna E.; Dotters-Katz, Sarah K. (American Journal of Perinatology, 2021)
Objective We aimed to assess the risk of developing gestational diabetes mellitus (GDM) in women with a normal A1C (<5.7) compared with those with an A1C in the pre-diabetic range (5.7–6.4).Study Design This study comprises of a retrospective cohort of non-anomalous singleton pregnancies with maternal body mass index (BMI) ≥40 at a single institution from 2013 to 2017. Pregnancies with multiple gestation, late entry to care, type 1 or 2 diabetes, and missing diabetes-screening information were excluded. The primary outcome was development of GDM. Secondary outcomes included fetal growth restriction, macrosomia, gestational age at delivery, large for gestational age, delivery BMI at delivery, total weight gain in pregnancy, induction of labor, shoulder dystocia, and cesarean delivery. Bivariate statistics were used to compare demographics, pregnancy complications, and delivery characteristics of women who had an early A1C < 5.7 and A1C 5.7 to 6.4. Multivariable analyses were used to estimate the odds of the primary outcome.Results Eighty women (68%) had an early A1C <5.7 and 38 (32%) had a A1C 5.7 to 6.4. Women in the lower A1C group were less likely to be Black (45 vs. 74%, p = 0.01). No differences in other baseline demographics were observed. The median A1C was 5.3 for women with A1C < 5.7 and 5.8 for women with A1C 5.7 to 6.4 (p < 0.001). GDM was significantly more common in women with A1C 5.7 to 6.4 (3.8 vs. 24%, p = 0.002). Women with pre-diabetic range A1C had an odd ratio of 11.1 (95% CI 2.49–48.8) for GDM compared with women with a normal A1C.Conclusion Women with class III obesity and a pre-diabetic range A1C are at an increased risk for gestational diabetes when compared with those with a normal A1C in early pregnancy.Key Points
Keywords: BMI; gestational diabetes; hemoglobin A1c; glucola; screening; obesity